The value ground of nursing - Snellman, Ingrid (Nursing ethics, 2012)
The aim of this literature study was to suggest a value ground for nursing anchored in two ethical principles: the principle of human value and the right to experience a meaningful life. Previous nursing research between the years 2000 and 2009 was analysed. Presented values suggested in this value ground are thus in line with the nursing context and science of today. Statements within ethical literature have been used in order to formulate arguments aimed at supporting the values that were found in the study. In the literature study six values were found: trust, nearness, sympathy, support, knowledge and responsibility. These values hold equal status and are not presented in hierarchical order. They vary due to the persons involved, nursing situations and cultural surroundings, but have the common requirement of being non-excluding. In order to implement the values within the value ground, two prerequisites are discussed and claimed as essential: ethical dialogue and a caring encounter between care provider and patients.